نظام المعلومات المحاسبي كأداة لتحقيق الميزة التنافسية في المؤسسة الإقتصادية دراسة ميدانية مؤسسة مولاي وأولاده للمشروبات - تاج هناء; مشراوي وفاء; قرادي عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
Currently the environment of the economical business knows various changes, as well as the technical development. Competing augments progressively according to the time, and the products become old with a minimum time. The economical businesses do not remain isolated from the impact of this change, the obliges of the research for a competitive advantage that induces the promotion of competitor, it aims at acquiring resources for the continuous development of work with a means of technological innovation. For this study puts to acquire the economical business a competitive advantage, it is necessary to ask for supply with the internal and external resources, and the technological innovation, it inclines to the development of the advantage of a different product, and they did continuous technological innovation to develop your competitive advantage with a developed objective.